2011
DOI: 10.1016/j.dss.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

A note comparing support vector machines and ordered choice models’ predictions of international banks’ ratings

Abstract: We find that Support Vector Machines virtually always predict international bank ratings better than ordered choice models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…external rating process such as linear regression (Horrigan 1996;West 1970), linear discriminant analysis (Pinch and Mingo 1973, 1 975), logit and probit (Altman and Katz 1976;Jackson and Boyd 1988) ordered logit and ordered probit (Kamstra et al 2001;Altman and Rijken 2004;Amato and Furfine 2004;Alejandro and Analía 2008;Bellotti et al 2011b), artifical intelligence techniques (Dutta and Shekhar 1988;Surkan and Singleton 1990;Kim et al 1993;Kwon et al 1997). Kim (2005), Huang et al (2004 and Lee (2007) show that artificial intelligence techniques (particularly neural networks and support vector machines) do not provide superior predictions of bond ratings compared with standard ordered-choice methods.…”
Section: Many Methodologies Have Been Developed In Recent Years Whichmentioning
confidence: 99%
“…external rating process such as linear regression (Horrigan 1996;West 1970), linear discriminant analysis (Pinch and Mingo 1973, 1 975), logit and probit (Altman and Katz 1976;Jackson and Boyd 1988) ordered logit and ordered probit (Kamstra et al 2001;Altman and Rijken 2004;Amato and Furfine 2004;Alejandro and Analía 2008;Bellotti et al 2011b), artifical intelligence techniques (Dutta and Shekhar 1988;Surkan and Singleton 1990;Kim et al 1993;Kwon et al 1997). Kim (2005), Huang et al (2004 and Lee (2007) show that artificial intelligence techniques (particularly neural networks and support vector machines) do not provide superior predictions of bond ratings compared with standard ordered-choice methods.…”
Section: Many Methodologies Have Been Developed In Recent Years Whichmentioning
confidence: 99%
“…Many methodologies have been developed in recent years which analyze the external rating process such as linear regression (Horrigan, 1966;West, 1970), linear discriminant analysis (Pinches and Mingo, 1973, 1975), logit and probit (Altman and Katz, 1976Jackson and Boyd, 1988) ordered logit and ordered probit (Kamstra et al, 2001;Altman and Rijken, 2004;Amato and Furfine, 2004;Alejandro and Analía, 2008;Bellotti et al, 2011b), artificial intelligence techniques (Dutta and Shekhar, 1988;Surkan and Singleton, 1990;Kim et al, 1993;Kwon et al, 1997). Kim (2005), Huang et al (2004) and Lee (2007) show that artificial intelligence techniques (particularly neural networks and support vector machines) do not provide superior predictions of bond ratings compared with standard ordered-choice methods.…”
Section: Credit Rating Determinantsmentioning
confidence: 99%
“…Bellotti and Crook (2009) compared LR and SVM, but without showing the feature selection method for the LR. Bellotti, Matousek, and Stewarti (2011) compared LR with SVM, but for regression purposes, not for classification. They found that the SVM model outperforms LR.…”
Section: Introductionmentioning
confidence: 99%